2018
DOI: 10.1093/gbe/evy157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Adaptations for Sensing and Securing Prey and Insight into Amniote Genome Diversity from the Garter Snake Genome

Abstract: Colubridae represents the most phenotypically diverse and speciose family of snakes, yet no well-assembled and annotated genome exists for this lineage. Here, we report and analyze the genome of the garter snake, Thamnophis sirtalis, a colubrid snake that is an important model species for research in evolutionary biology, physiology, genomics, behavior, and the evolution of toxin resistance. Using the garter snake genome, we show how snakes have evolved numerous adaptations for sensing and securing prey, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 125 publications
(165 reference statements)
3
89
0
Order By: Relevance
“…However, we confirm that geckos do appear to have lost at least three rod phototransduction genes, including rod phosphodiesterases (PDE6B and PDE6G), and the alpha subunit of the rod cyclic nucleotide gated channel (CNGA1), because these were not found in the eye transcriptomes or any of the gecko genomes. As previously noted, two genes, PDE6A and GNGT1, were found to be absent in all reptiles, but present in mammals, amphibians, and fishes Perry et al 2018). A second gene, SLC24A1, was found to be absent in all squamates, but is present in other vertebrate groups.…”
Section: Genessupporting
confidence: 65%
See 1 more Smart Citation
“…However, we confirm that geckos do appear to have lost at least three rod phototransduction genes, including rod phosphodiesterases (PDE6B and PDE6G), and the alpha subunit of the rod cyclic nucleotide gated channel (CNGA1), because these were not found in the eye transcriptomes or any of the gecko genomes. As previously noted, two genes, PDE6A and GNGT1, were found to be absent in all reptiles, but present in mammals, amphibians, and fishes Perry et al 2018). A second gene, SLC24A1, was found to be absent in all squamates, but is present in other vertebrate groups.…”
Section: Genessupporting
confidence: 65%
“…photoreceptors were modified to resemble the appearance, and function, of cones (Schott et al 2016;Simões et al 2016;Bhattacharyya et al 2017;Perry et al 2018). However, caenophidian snakes possess many different retinal types (ranging from duplex, to all-cone, to all-rod) distributed among independent phylogenetic lineages.…”
mentioning
confidence: 99%
“…These proteins have molecular masses of 13-15 kDa and are classified into groups I and II, which are found as major components in the venoms of Elapidae and Viperidae, respectively (Six and Dennis, 2000;Harris and Scott-Davey, 2013). In addition, a third group of PLA2s, termed IIE, have been predominately recovered from the venoms of nonfront fanged snakes, although their importance in the venom arsenal remains unclear (Fry et al, 2012;Perry et al, 2018). Studies reconstructing the evolutionary history of this multilocus gene family have demonstrated that each of these PLA2s types (I, II, and IIE) have been independently recruited into snake venom systems (Fry et al, 2012;Junqueira-De-Azevedo et al, 2015), suggesting they have evolved their toxic properties by convergent evolution (Lomonte and Rangel, 2012).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 99%
“…Ophiophagus hannah 1 (Vonk et al 2013), Thamnophis sirtalis 1 (Perry et al 2018), and Pantherophis guttatus 1 (Ullate-Agote et al 2014), and the lizards Gekko japonicus 1 , Eublepharis macularius 2 (Xiong et al 2016), Correlophus ciliatus 3 , Christinus marmoratus 3 , Dopasia gracilis 2 (Song et al 2015), Pogona vitticeps 2 (Georges et al 2015), and Anolis carolinensis 1 (Alföldi et al 2011). At the time of data acquisition, three more squamate species genomes were available for Thamnophis elegans (Vicoso et al 2013), Sistrurus miliarus (Vicoso et al 2013), and Sceloporus occidentalis (Genomic Resources Development Consortium et al 2015), though due to short read lengths and/or missing data, we chose not to use them (the purpose of these studies was not to acquire the high coverage or long read lengths needed for our purposes).…”
Section: Squamate Genomesmentioning
confidence: 99%